Financial Health Assessment of Bank BRI: Trends in Liquidity, Profitability, and Management Efficiency - Riu, Isma Azis (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Banking is the backbone of the construction of Indonesia's economic and financial system. A variety of economic issues greatly affect the business world, especially banking, where companies compete to perform well. Several metrics can be used to assess a bank's financial performance, such as the bank's financial statement performance. Financial reports are one of the information media that can provide an overview of a bank's health. The purpose of this study is to "research and understand PT's financial performance." Based on bank BRI Persero, Tbk, liquidity ratio, solvency ratio and profitability ratio. The study uses descriptive and quantitative methods by measuring liquidity, solvency and profitability ratios. Results based on liquidity ratio using quick ratio, bank. One Belt, One Road has sufficient capital to guarantee both short-term and long-term debt. Based on the indicators of NPM, ROE and ROA, the rate of return has decreased for five years due to the bank management's inability to manage assets to increase sales. Gross margin has increased for five years in a row, and BRI has been able to minimize costs and generate high gross margins, which is healthy. NPM, ROE and ROA have all declined, but profitability metrics remain healthy as they comply with BI's overall credit rating criteria. In order to increase this ratio, banks need to evaluate their business performance and appropriately improve their lending and asset management.